Modulasi Mikrobiota untuk Memperbaiki Laju Filtrasi Glomerulus, Toksin Uremik, dan Penanda Inflamasi pada Gagal Ginjal Kronik: Telaah Sistematik dan Meta-Analisis - Gunawan, Burhan; Purwata, Raymond Sebastian; Hidayat, Syarif; Pandapotan, Roy Akur; Jennifer, Jennifer (UI Scholars Hub, 2023)
Introduction. Dysbiosis microbiota is considered as one of the consequences and impacts of high uremic toxins in patients with Chronic Kidney Disease (CKD), which can lead to an increased risk of progression and mortality. The aim of this systematic review and meta-analysis was to perform quantitative effect of microbiota modulation for estimated Glomerular Filtration Rate (eGFR), uremic toxin (total-p cresyl/total pCS), and inflammatory marker (hs-CRP) outcome among CKD patients. Methods. Article searches were conducted from PubMed, ScienceDirect, and Cochrane Library data sources from 2010-2022. Assessment of article quality follows the rules of PRISMA (Preferred Reporting Items in Systematic Review and Meta-Analysis). Only randomized controlled trial (RCT) articles investigating the effect of symbiotic, prebiotic, of probiotic for CKD were included in the analysis. Effect size quantify from Standardized Mean Difference (SMD), using a continuous random effect model and described in the forest plot model. Results. A total of 17 RCT studies with a total 867 CKD stage 1-5 subjects (440 subjects in the intervention group and 427 subjects in the control group). The intervention duration ranging from 1-12 months. The studies included had varied on methodologies, with significant heterogenicity (I296,96%, p Conclusions. The administration of probiotic/prebiotic/symbiotic supplements to CKD patients resulted in significant improvements in e-GFR and reductions in total pCS. These results suggest the potential of symbiotic, prebiotic, and probiotic supplementation to improve CKD outcome. Keywords: Chronic kidney disease, e-GFR, hs-CRP, prebiotic, probiotic, uremic toxin